PENERAPAN MODEL PEMBELAJARAN KRATHWOLH DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IX DI SMP NASIONAL MAKASSAR - Dwiyanti; Nur Aslindawaty (Jurnal Ilmiah Global Education, 2022)
This research is classroom action research carried out in 2 cycles and through several stages in each cycle, namely: planning, implementation, observation, and reflection. The purpose of this research is to improve students’ learning achievement through the application of the Krathwohl learning model in Class IX at SMP Nasional Makassar. The data collection was carried out using observation sheets and end-of-cycle tests. The collected data will be analyzed and equipped with a frequency table. The results of this study showed that there was an improvement in students’ learning activity in the first cycle with 41.91%, and an increase in the second cycle, which was 77.77%. As well as an increase in the completeness of student learning outcomes in cycle I with a total of 15 students with a percentage of 45.45% and an increase in cycle II with a total of 27 students with a percentage of 80% with a total of 33 students. Thus, it can be indicated that the application of the Krathwohl learning model in class IX at SMP Nasional Makassar. can improve learning achievement.